SYNTHESIS OF ULTRA-FINE CRYSTALLINE ZRXTI1-XO4 POWDER BY POLYMERIC PRECURSOR METHOD - Cerqueira, M.; Nasar, R. S.; Longo, Elson [UNESP]; Leite, E. R.; Varela, José Arana [UNESP] (Elsevier B.V., 1995)
Reactive ZrxTi1-xO4 (x=0.65, 0.50 and 0.35) powder was prepared by the polymeric precursor method. Studies by X-ray diffraction (XRD), nitrogen adsorption/desorption, and thermogravimetric analysis (TG) showed that powders with high crystallinity (>90%) and high surface areas (>40 m(2)/g) are obtained after calcination at 700 degrees C for 3 h. Infrared spectroscopy and XRD results showed that these titanates nucleate from the amorphous phase with no intermediate phases, at low temperature (450 degrees C).